Extracellular Paracoccidioides brasiliensis phospholipase B involvement in alveolar macrophage interaction - Soares, Deyze Alencar (2010)
Background: Phospholipase B (PLB) has been reported to be one of the virulence factors for human pathogenic fungi and has also been described as necessary for the early events in infection. Based on these data, we investigated the role of PLB in virulence and modulation of the alveolar pulmonary immune response during infection using an in-vitro model of host-pathogen interaction, i.e. Paracoccidioides brasiliensis yeast cells infecting alveolar macrophage (MH-S) cells. Results: The effect of PLB was analyzed using the specific inhibitor alexidine dihydrochloride (0.25 μM), and pulmonary surfactant (100 μg mL-1), during 6 hours of co-cultivation of P. brasiliensis and MH-S cells. Alexidine dihydrochloride inhibited PLB activity by 66% and significantly decreased the adhesion and internalization of yeast cells by MH-S cells. Genes involved in phagocytosis (trl2, cd14) and the inflammatory response (nfkb, tnf-α, il-1β) were down-regulated in the presence of this PLB inhibitor. In contrast, PLB activity and internalization of yeast cells significantly increased in the presence of pulmonary surfactant; under this condition, genes such as clec2 and the pro-inflammatory inhibitor (nkrf) were up-regulated. Also, the pulmonary surfactant did not alter cytokine production, while alexidine dihydrochloride decreased the levels of interleukin-10 (IL-10) and increased the levels of IL-12 and tumor necrosis factor-α (TNF-α). In addition, gene expression analysis of plb1, sod3 and icl1 suggests that P. brasiliensis gene re-programming is effective in facilitating adaptation to this inhospitable environment, which mimics the lung-environment interaction. Conclusion: P. brasiliensis PLB activity is involved in the process of adhesion and internalization of yeast cells at the MH-S cell surface and may enhance virulence and subsequent down-regulation of macrophage activation.